Manajemen Kelas Merdeka Belajar Untuk Meningkatkan Jumlah Siswa Dalam Proses Pembelajaran - Sakhiatun Sarah; Supriadi Supriadi (Program Studi PGSD Kampus UPI di Serang, 2021)
This study aims to find problems in the online learning process in class iv sdn 024757 binjai city with the hope that all students in class iv can follow the online learning process by making class agreements involving teachers, students, and parents that refer to the principle of independent learning. The method used in this research is field research by conducting research studies on actual conditions through observations and interviews related to classroom management during online learning. The research techniques used in this study were interviews, observation, and documentation studies. By making a free learning class agreement, it can foster effective communication between teachers, students, and parents. In addition, it fosters a sense of responsibility for students to participate in the online learning process because previously students have been involved in determining the expected class.